Melt growth and properties of bulk BaSnO3 single crystals. (29th December 2016) - Galazka, Z; Uecker, R; Irmscher, K; Klimm, D; Bertram, R; Kwasniewski, A; Naumann, M; Schewski, R; Pietsch, M; Juda, U; Fiedler, A; Albrecht, M; et al.
Abstract: We present the first-time growth of bulk BaSnO3 single crystals from the melt by direct solidification, their basic electrical and optical properties as well as their structural quality. Our measurement of the melting point (MP) of BaSnO3 amounts to 1855 °C  ±  25 K. At this temperature an intensive decomposition and non-stoichiometric evaporation takes place as the partial pressure of SnO(g) is about 90 times higher than that of BaO(g). X ray powder diffraction identified only the BaSnO3 perovskite phase, while narrow rocking curves having a full width at half maximum of 26 arcsec and etch pit densities below 10 6 cm −2 confirm a high degree of structural perfection of the single crystals. In this respect they surpass the structural properties of those single crystals that were reported in the literature. The electrical conductivity of nominally undoped crystals depends on the growth conditions and ranges from insulating to medium n -type conductivity. After post-growth annealing in an oxidizing atmosphere undoped crystals are generally insulating. Doping the crystals with lanthanum during growth results in a high n -type conductivity. For a La doping concentration of 0.123 wt.% we measured an electron concentration of 3.3  ×  10 19 cm −3 and an electron mobility of 219 cm 2 V −1 s −1 . Based on optical absorption measurements we determined an energy of 3.17  ±  0.04 eV at 5 K and of 2.99  ±  0.04 eV at 297 K for the indirect band gap of BaSnO3 .